CHARACTERISTIC OF TEAM IN SUCCESSFUL STARTUP ENTREPRENEUR IN THAILAND - Hongsirikarn, Kitima; Wongvanichtawee, Chalermkiat; Santisarn, Burin (RMUTT Global Business and Economics Review, 2020)
This research studied the characteristic of team in successful startup business through documentary research and qualitative research. The changing in business management impacted on the people management within organization. In the past, the organization management focused on how to set the system, create the standard structure as a whole, manage the people through manager and staff relationship. However, the new way of running the business under Thai’s Government support named “Startups” required a new way of managing people as a leader and team. This business required a competent person who not only had skills, creativity, and being a good problem solver but also could work as a team. The literature review showed that the characteristics of successful team included communication skills among team and leader, loyalty and commitment; and the same direction and trust among team member. After the researcher had employed qualitative research by in-depth interview of 32 people and a focus group of 7 people, the results showed that all characteristics mentioned above were all relevant for successful team member. However, a new finding, initiative, was also discovered. Consequently, this research could be concluded that the conceptual framework of successful startup team member in Thailand was associated with 5 characteristics factors: communication, loyalty and commitment, the same goal and direction, trust and initiative.